Taper Quality Evaluation of a Laser Lathed Steel Rod Using Modified Flatbed CO2 Laser Cutting Machine - Sivarao, Subramonian; Abdul , Zuhair; Raja, izam; Mohd , amran; Nur, izan; Mohd , Hadzley (2012)
CO2 flatbed laser cutting machine is one of the advanced machining processes which is capable of machining various materials especially super hard engineered materials. The available CO2 flatbed laser cutting machine is only able to flat worksheets. This paper presents the laser lathing quality, particularly taper of cylindrical steel rod using 2D flatbed CO2 laser cutting machine. A specially designed spinning device mechanism was developed to clamp and spin a steel rod of 10 mm diameter. Three significant cutting parameters were controlled in this experiment, namely; cutting speed, spinning speed and depth of cut. The experiments were carried out based on full factorial DOE matrix design. The results show that, laser lathing is capable of improving almost 80-90 percent as compared to manual lathing within the same range of workpiece properties and dimensional accuracy